Biomarkers of alcohol misuse: recent advances and future prospects - Jastrzębska, Iwona; Zwolak, Agnieszka; Szczyrek, Michał; Wawryniuk, Agnieszka; Skrzydło-Radomańska, Barbara; Daniluk, Jadwiga (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Alcohol abuse and dependence are highly prevalent in many cultures and contribute considerably to the global burden of health and social issues. The current inability to accurately characterise long-term drinking behaviours is a major obstacle to alcoholism diagnosis and treatment. Therefore, it is of great importance to develop objective diagnostic tools to discern subjects with excessive alcohol use and alcoholism or to confirm abstinence. Research over past years has revealed several biochemical compounds with considerable potential for accurate reflection of alcohol intake. This review will address the issue of alcohol biomarker definition, the types of molecules used as so-called traditional biomarkers, and the compounds that can serve as novel biomarker candidates or components of biomarker panels.